2022
DOI: 10.3324/haematol.2022.280995
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule SUMO inhibition for biomarker-informed B-cell lymphoma therapy

Abstract: Aberrant activity of the SUMOylation pathway has been associated with MYC overexpression and poor prognosis in aggressive B-cell lymphoma (BCL) and other malignancies. Recently developed small molecule inhibitors of SUMOylation (SUMOi) target the heterodimeric E1 SUMO activation complex (SAE1/UBA2). Here, we report that activated MYC signaling is an actionable molecular vulnerability in vitro and in a pre-clinical murine in vivo model of MYCdriven BCL. While SUMOi conferred direct effects on MYC-driven lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Hence, the molecular mechanisms underlying the strong and rapid induction of IFNB by TAK-981 remain to be identified. TAK-981-induced IFN-I response was suggested to play a critical role in its anti-tumoral activity through its ability to activate both innate and adaptative anti-tumoral immune responses (10)(11)(12)(13)29). Accordingly, TAK-981 was found to enhance the antitumoral activity of monoclonal antibodies as seen for rituximab (anti-CD20) or daratumumab (anti CD38) in preclinical mouse models of lymphoma and myeloma respectively (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the molecular mechanisms underlying the strong and rapid induction of IFNB by TAK-981 remain to be identified. TAK-981-induced IFN-I response was suggested to play a critical role in its anti-tumoral activity through its ability to activate both innate and adaptative anti-tumoral immune responses (10)(11)(12)(13)29). Accordingly, TAK-981 was found to enhance the antitumoral activity of monoclonal antibodies as seen for rituximab (anti-CD20) or daratumumab (anti CD38) in preclinical mouse models of lymphoma and myeloma respectively (11).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the overexpression of innate immunity activating ligands by cancer cells, recent studies have reported that inhibition of SUMOylation with TAK-981 activates an anti-tumor immune response and improves the efficiency of immune therapies by directly affecting immune cells. In models of pancreatic cancer and lymphomas, TAK-981 activates CD8 T-cells, NK cells, monocytes and dendritic cells (10)(11)(12)(13), and decreases regulatory T-cells (T-reg) differentiation (14). The immuno-modulatory function of TAK-981 was suggested to rely on its ability to induce type-I Interferon (IFN-I) secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the highly effective SUMOi subasumstat/TAK‐981 is currently undergoing early clinical phase testing in lymphoma and further cancer entities. Several studies have already shown the successful application of SUMOi in a variety of cancers, such as pancreatic cancer and BCL (Hoellein et al , 2014 ; Biederstadt et al , 2020 ) and that subasumstat can act via activation of the immune system (Lightcap et al , 2021 ; Demel et al , 2022 ; Kumar et al , 2022 ) or direct killing of tumor cells (Biederstadt et al , 2020 ; Demel et al , 2023 ). Importantly, we here report SLF2 loss as an actionable biomarker for BCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Indeed, TAK-981 activates dendritic cells, cytotoxic CD8 + T cells, memory B cells, natural killer (NK) cells and macrophages. [20][21][22][23][24] Moreover, TAK-981 increases antigen presentation by cancer cells, further enhancing anti-tumor immune response. 22 In addition to these effects on the immune micro-environment, TAK-981 can directly induce cancer cells death.…”
Section: Introductionmentioning
confidence: 99%